PROMOTING EMPLOYMENT OPPORTUNITIES IN SOUTH KOREA AT SMK TELEKOMUNIKASI BRAWIJAYA BLITAR - Darmanto, Darmanto; Dewi, Ekka Zahra Puspita; Muliawan, Anugrah Adi; Hakim, Lukman; Kristanto, Nanak; Wulandari, Romadhani; Setiawan, Dedi; Pradana, Mohammad Alfian Radita; Nengrum, Yeny Septi (Jurnal Pengabdian Masyarakat Sabangka, 2025)
This article discusses a community service initiative implemented by Universitas Madani Indonesia in collaboration with SMK Telekomunikasi Brawijaya Blitar to promote employment opportunities in South Korea. The program responds to increasing global labor mobility and Indonesia's need to prepare vocational school graduates for overseas employment. Using a three-stage model—planning, implementation, and evaluation—the program included a socialization session that introduced students to the Employment Permit System (EPS), job requirements, language training, and cultural adaptation. The initiative successfully engaged students and addressed their concerns about rights, responsibilities, and challenges related to working abroad. The findings emphasize the importance of early preparation, institutional partnerships, and curriculum integration to equip students with global competencies. The program reflects a paradigm shift in vocational education toward international employability and offers a replicable model for future community outreach and workforce development efforts.